Sitagliptin and the Blood-Retina Barrier: Effects on Retinal Endothelial Cells Manifested Only after Prolonged Exposure - Anja Jäckle; Focke Ziemssen; Eva-Maria Kuhn; Jürgen Kampmeier; Gerhard K. Lang; Gabriele E. Lang; Helmut Deissler; Heidrun L. Deissler (Journal of Diabetes Research)
Inhibitors of dipeptidyl peptidase-4 (DPP-4) are widely used to treat diabetes mellitus, but data concerning their effects on the barrier stability of retinal endothelial cells (REC) in vivo and in vitro are inconsistent. Therefore, we studied whether the barrier properties of immortalized endothelial cells of the bovine retina (iBREC) were affected by the inhibitors of DPP-4 sitagliptin (10-1000 nM) and diprotin A (1-25 μM). Their effects were also investigated in the presence of VEGF-A165 because diabetic patients often develop macular edema caused by VEGF-A-induced permeability of REC. To detect even transient or subtle changes of paracellular and transcellular flow as well as adhesion of the cells to the extracellular matrix, we continuously monitored the cell index (CI) of confluent iBREC grown on gold electrodes. Initially, the CI remained stable but started to decline significantly and persistently at 40 h or 55 h after addition of sitagliptin or diprotin A, respectively. Both inhibitors did not modulate, prevent, or revert the persistent VEGF-A165-induced reduction of the CI. Interestingly, sitagliptin and diprotin A increased the expression of the tight-junction protein claudin-1 which is an important component of a functional barrier formed by iBREC. In contrast, expressions of CD29—a subunit of the fibronectin receptor—or of the tetraspanin CD9 were lower after extended treatment with the DPP-4 inhibitors; less of the CD9 was seen at the plasma membrane after prolonged exposure to sitagliptin. Because both associated proteins are important for adhesion of iBREC to the extracellular matrix, the observed low CI might be caused by weakened attachment of the cells. From our results, we conclude that extended inhibition of DPP-4 destabilizes the barrier formed by microvascular REC and that DPP-4 inhibitors like sitagliptin do not counteract or enhance a VEGF-A165-induced barrier dysfunction as frequently observed in DME.